2006
DOI: 10.1007/s10616-006-9035-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth control of hybridoma cells with an artificially induced EpoR-gp130 heterodimer

Abstract: IL-6 has been known to modulate the growth of many hybridoma cells and also promote resultant antibody productivity. However, IL-6 is so expensive that the use of IL-6-dependent hybridomas for industrial antibody production is not practical. In this study, we aimed at designing antibody/gp130 and antibody/EpoR chimeras which could tightly control cell growth in response to more affordable cognate antigen. Retroviral vectors encoding V H or V L region of anti-hen egg lysozyme (HEL) antibody HyHEL-10 tethered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…As one of many such examples, replacing the ECD of the erythropoietin (Epo) receptor (EpoR) with those of epidermal growth factor receptor (EGFR), insulin-like growth factor receptor (IGFR), or c-Kit produces an active construct that induces STAT5 phosphorylation and Ba/F3 proliferation in a ligand-dependent manner (Ohashi, Maruyama, Liu, & Yoshimura, 1994). Similarly, fusion of the gp130 ICD to EpoR ECD leads to Epo-mediated activation of STAT1 and STAT3, consistent with activation of the full-length gp130 by its native ligands (Kawahara et al, 2006; Schaeffer et al, 2001). Other examples of receptor ectodomain swapping have been reported for the type I IFN (Pattyn et al, 1999) and IL-4/IL-13 (Fujiwara, Hanissian, Tsytsykova, & Geha, 1997; Heller et al, 2012) systems, and in all cases, the chimeric receptors elicit some extent of activation of the expected Jak/STAT signaling molecules.…”
Section: Ligand–receptor Complex Formation: Geometry and Affinitysupporting
confidence: 59%
“…As one of many such examples, replacing the ECD of the erythropoietin (Epo) receptor (EpoR) with those of epidermal growth factor receptor (EGFR), insulin-like growth factor receptor (IGFR), or c-Kit produces an active construct that induces STAT5 phosphorylation and Ba/F3 proliferation in a ligand-dependent manner (Ohashi, Maruyama, Liu, & Yoshimura, 1994). Similarly, fusion of the gp130 ICD to EpoR ECD leads to Epo-mediated activation of STAT1 and STAT3, consistent with activation of the full-length gp130 by its native ligands (Kawahara et al, 2006; Schaeffer et al, 2001). Other examples of receptor ectodomain swapping have been reported for the type I IFN (Pattyn et al, 1999) and IL-4/IL-13 (Fujiwara, Hanissian, Tsytsykova, & Geha, 1997; Heller et al, 2012) systems, and in all cases, the chimeric receptors elicit some extent of activation of the expected Jak/STAT signaling molecules.…”
Section: Ligand–receptor Complex Formation: Geometry and Affinitysupporting
confidence: 59%
“…For JAK/STAT cytokine receptors, it has been previously established that genetically modified chimeric receptors in which the extracellular domain (ECD) of a cytokine receptor has been fused with the intracellular domain (ICD) of a different receptor activated signaling in a ligand-dependent manner ( Fujiwara et al, 1997 ; Heller et al, 2012 ; Kawahara et al, 2006 ; Ohashi et al, 1994 ; Pattyn et al, 1999 ; Schaeffer et al, 2001 ). However, for this concept to be practically useful, soluble ligands that co-opt endogenous receptors and assemble non-natural dimers on natural cells and tissues are required.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is full of studies arguing in favour of both models, making it difficult to navigate and draw strong conclusions. Early studies using chimeric cytokine‐receptors, where the ECD of a cytokine receptor was swapped with the ECD of another cytokine receptor, suggested that the topological requirement for signal activation by cytokines are quite lax [ 142 , 143 , 144 , 145 , 146 ]. In all studies, the chimeric receptor triggered signalling to levels comparable to those induced by the wild‐type receptor.…”
Section: Cytokine‐receptor Complex Stability/kinetics and Signallingmentioning
confidence: 99%